2012
DOI: 10.1091/mbc.e11-12-0994
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol content specifies targeting of tail-anchored proteins to mitochondrial outer membranes

Abstract: Mitochondrial outer membrane tail-anchored proteins are a unique class of membrane proteins with unknown targeting mechanism. Using two high-throughput microscopy screens, we demonstrate that the inherent differences in membrane composition between organelle membranes is enough to determine membrane integration specificity in a living cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 55 publications
4
134
0
Order By: Relevance
“…In the latter cases, mitochondria were usually aggregated, probably due to the elevated levels of GFP-Om14 in the MOM. However, in contrast to mutants that affect targeting of MOM single-span proteins (33,34), none of the inspected strains displayed mistargeting to other organelles. Manually annotating the resulting images for changes in localization or automatically extracting intensity data, we could find 146 strain backgrounds with altered intensity and/or altered localization of the GFP construct (see Table S1 in the supplemental material).…”
Section: Gfp-om14 Serves As a Model Protein For Correct Membrane Insementioning
confidence: 85%
“…In the latter cases, mitochondria were usually aggregated, probably due to the elevated levels of GFP-Om14 in the MOM. However, in contrast to mutants that affect targeting of MOM single-span proteins (33,34), none of the inspected strains displayed mistargeting to other organelles. Manually annotating the resulting images for changes in localization or automatically extracting intensity data, we could find 146 strain backgrounds with altered intensity and/or altered localization of the GFP construct (see Table S1 in the supplemental material).…”
Section: Gfp-om14 Serves As a Model Protein For Correct Membrane Insementioning
confidence: 85%
“…Similarly, it has been shown that downregulation of genes involved in ergosterol biosynthesis leads to a severe mitochondrial morphology phenotype , suggesting an important role of ergosterol in overall organelle morphogenesis. Furthermore, the proper membrane integration of some single-span mitochondrial MOM proteins requires a low ergosterol content of the membrane (Kemper et al, 2008;Krumpe et al, 2012;Merklinger et al, 2012). Moreover, it is tempting to assume that the function of protein translocases and especially insertases depends on the biophysical properties of the membrane they are embedded in and therefore on the lipid composition of these membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown whether a protein-based machinery exists for the insertion of C-terminally anchored (tail-anchored) proteins into the outer membrane. It appears that the lipid composition of the outer membrane is a major requirement for integrating of the tail-anchored proteins (64)(65)(66). Interestingly, in the case of Tom22, the receptor and organizer of TOM that is also C-terminally anchored, a requirement for both the TOM and SAM complexes for its biogenesis has been demonstrated (67).…”
Section: Specific Transport Pathways and Their Interplays With Major mentioning
confidence: 99%